Temperature Measuring Method Accuracy Evaluation in the Microarc Heating Process Based on Reproducibility and Uncertainty Indicators - M. S. Stepanov; I. G. Koshlyakova (Приборы и методы измерений)
It is necessary to control temperature using thermoelectric sensors for steel products surface alloying in conditions of microarc heating. The using S-type thermocouples possibility has been substantiated, main factors affecting the measurement results have been established, and the the reproducibility index functional dependence on the measured temperature has been determined, as a result of previous studies. However, additional influencing factors that may affect to the heating process kinetics and the temperature measurements results were not taken into account. The purpose of the work was a steel temperature measurement results uncertainty generalized assessment during microarc heating, taking into account most complete influencing factors set. Influencing factors comprise: average coal powder particle size (X1), sample diameter (X2); chromium content in steel (X3 ). The measurement error was denoted Y. The dependence is obtained: Y = –4.032X1 – 0.095X2 + 0.0058X3 + 3.414. Thus, in the studied range of values, an increase in the powder particle and the samples diameter size leads to a decrease in the measurement error, and the chromium content increase leads to its increase. Therefore, the temperature measurement error during microarc heating can be reduced with decrease the sample heating rate, as well as with increase the heat transfer intensity from its surface to the material depth due to an increase the size, and, accordingly, the processed products mass. Next, the studied factors values distribution laws were evaluated. For X1 and X2, the normal distribution law is adopted, for X3 – uniform. Taking into account each factor's influence coefficients, and the total uncertainty estimate introduced assessment by them, a generalized uncertainty estimate was found: U = 1.1 °C. The microarc heating temperature measurement method quantitative assessment detailed of the accuracy makes it possible to take into account all significant influencing factors and their total measurement uncertainty contribution. The obtained temperature measurement's total uncertainty value from the three studied factors can be used as a priori information as a type B uncertainty during the microarc saturation process.